Assessing the effectiveness of The Extraordinary Territorial Public Health Commissions coordination mechanisms in the COVID-19 response in Republic of Moldova: coordination and capacity gaps - Daniela DEMISCAN (One Health & Risk Management)
Introduction. The COVID-19 pandemic highlighted the need for effective coordination in managing health crises. In the Republic of Moldova, the response was managed by the National Extraordinary Public Health Commissions but implemented by the Extraordinary Territorial Public Health Commissions (TEPHCs).